Depression, Anxiety, and Stress in Undergraduate Allied Health Students: A Cross-Sectional Study from Multan, Pakistan: Depression, Anxiety, and Stress in Undergraduate Allied Health Students - Ahmad, Ayyan; Sultan, Mohsin; Irfan, Sameeha; Mehboob, Khuram; Sultan, Ansa; Naeem, Insha; Shehzad, Sheeraz (THE THERAPIST (Journal of Therapies & Rehabilitation Sciences), 2025)
Mental health problems like depression, anxiety, and stress become more widespread in university students all over the world. The involvement of academic pressure, social pressure, and transitional life stages is one of the factors that build psychological distress that may affect academic performance and general well-being. Objectives: To determine the prevalence and severity of depression, anxiety, and stress among undergraduate students of allied health sciences pursuing their undergraduate degrees at Laeeque Rafique Institute of Health Sciences, Multan, Pakistan. Methods: A cross-sectional study was conducted from January 15 to April 20, 2024, including all students of LRIHS. Participants completed a two-part questionnaire comprising socio-demographic details and the standardized DASS-21 scale. Data were analyzed using SPSS version 26.0 to calculate frequencies, percentages, means, and standard deviations. Results: Depression prevalence was 3.43% extremely severe, 8.57% severe, 22.57% moderate, 18.29% mild, and 47.14% normal. Anxiety levels were 15.43% extremely severe, 8.57% severe, 23.43% moderate, 7.71% mild, and 44.86% normal. Stress was reported as 2.57% extremely severe, 10.86% severe, 15.71% moderate, 19.71% mild, and 51.14% normal. Female students showed higher stress levels, while male students had relatively higher rates of depression and anxiety. Conclusions: The results suggest that undergraduate allied health sciences students experience considerable psychological distress. These findings point to the necessity to invest in specific mental health support, screening, and intervention in academic institutions.